What Does it Matter? Factors in Occurrence of Elderly Abuse among Healthcare Workers in Nursing Homes: A Systematic Review - Anis Fauziah; Husna Ardiana; Diah Priyantini; Elok Faradisa; Inta Susanti; Tintin Sukartini; Retno Indarwati (Jurnal Ners, 2020)
Introduction: Elderly abuse appears to become an important public health concern and to be widely underestimated by health professionals. The cases are misunderstood and misreported, and often reported as fatal consequences of crimes toward elders. The aim of this review was to explore the factors in occurrence of elder abuse among healthcare workers in nursing homes.Methods: Seven databases, including Scopus, EBSCO, ProQuest, PubMed, CINAHL, Web of Science and ScienceDirect, were explored to search relevant articles. The initial keywords were “elderly” “abuse” “healthcare workers” and “nursing homes”. The search was limited to English and the data sources were limited to articles published from 2015-2020.Results: The perspective of the WHO’s integrated care for older people was used as a lens to discuss the results. Fourteen articles were involved in the review. This review suggests that healthcare workers in nursing homes do elder abuse because of their high workload and lack of knowledge around the topic.Conclusion: This finding acts as a contributor to the paucity of study about elder abuse among healthcare workers. The available evidence suggests that elder abuse has become a significant problem in nursing homes. It is indicated that elder abuse was never been a popular topic among the health workers in nursing homes.